Proportion and Outcome of Induction of Labor Among Mothers Who Delivered in Teaching Hospital, Southwest Ethiopia - Tewodros Yosef; Dawit Getachew (Frontiers Media S.A., 2021)
Background: Despite the induction of labor (IOL) having had some undesired consequences, it also has several benefits for maternal and perinatal outcomes. This study aimed to assess the proportion and outcome of IOL among mothers who delivered in Teaching Hospital, southwest Ethiopia.Methods: A retrospective cross-sectional study was conducted from June 10 to June 20, 2019, among 294 mothers who gave birth between November 30, 2018, and May 30, 2019, by reviewing their cards using a structured checklist to assess the prevalence, outcome, and consequences of induction of labor. A binary logistic regression analysis was computed to look for the association between outcome variables and independent variables.Results: The prevalence of labor induction was 20.4%. The most commonly reported cause of induction was preeclampsia (41.6%). The factors associated with IOL were mothers aged 25-34 years [AOR = 2.55, 95% CI (1.18-5.50)] and ≥35 years [AOR = 10.6, 95% CI (4.20-26.9)], having no history of antenatal care [AOR = 2.12, 95% CI (1.10-4.07)], and being Primipara AOR = 2.33, 95% CI (1.18-3.24)]. Of the 60 induced mothers, 23.3% had failed induction. The proportion of mothers with dead fetal outcomes and maternal complications was 5 and 41.7%, respectively. The unfavorable Bishop Score before induction [AOR = 1.85, 95% CI (1.32-4.87)] and induction using misoprostol [AOR = 1.48, 95% CI (1.24-5.23)] were the factors associated with failed induction of labor.Conclusion: The prevalence of induced labor was considerably higher than rates in other Ethiopian studies; however, the prevalence of induction failure was comparable to other studies done in Ethiopia. The study found that Bishop's unfavorable score before induction and induction using misoprostol was the factor associated with unsuccessful induction. Therefore, the health professionals should confirm the favorability of the cervical status before the IOL to increase the success rate of induction of labor.